Avtomatika v energetiki : Zbirka računalniških vaj - Srpčič, Gregor; Igrec, Dalibor (University of Maribor Press, 2022)
Automation in Energetics: Collection of Computer Exercises. This collection of computer exercises is intended primarily for Faculty of Energy Technology in Krško and Velenje students, as an additional teaching material in the curse Automation in Energetics in the undergraduate professionally oriented study programme and undergraduate academic study programme Energy Technology. Students solve the exercises by using Matlab/Simulink software package. The first three exercises represent a repetition and, at the same time, an introduction to working with the mentioned software package. The remaining computer exercises are related to the lectures and cover the following topics: differential equations, transfer functions, state-space representation, frequency characteristics, and open and closed-loop control systems. In order to successfully solve some of the computer exercises, it is necessary to know the methods for solving differential equations, converting state-space equations into a transfer function, and determining the mathematical model of the electrical circuit in state-space.